مواقف العلماء من الدولة الأموية في مرحلة التكوين والبناء ٤١-١٣٢هـ / ٦٦١-٧٥٠م: دراسة في الروايات التاريخية المبكرة: The Attitudes of Scholars on the Umayyad State during the Formation and Construction Stage 41-132 AH / 661-750 AD: A study on early Historical Narratives - Al-Tel, Othman Ismael (Journal of Al-Tamaddun, 2024)
The study deals with the attitudes of the Muslim scholars towards the Umayyad state. It addresses the attitudes of the scholars who opposed the Umayyad rule and refused to cooperate and deal with the state, in addition to their attitudes towards the issue of revolt (revolution). This attitude could be seen since they called to overthrow the Umayyad by participating in either some movements and revolutions, or by opposing these movements and calling the people to detach themselves from such movements through avoiding any participation with the state. This is in addition to their refusal to use force as a way of change because it might cause strife (fitna) among Muslims. The study also addresses the attitude of the scholars, who provided the Umayyad rulers with advice and guidance, and tried to direct them towards highest values of Islam through achieving justice and equality among people. The study also tackles the attitudes of those jurists whom supported strongly and stood by the state though holding and assuming important positions, including judiciary in particular, as they considered the Umayyad state the legitimate one that should not be opposed in whatever way including the revolution.